2002
DOI: 10.1055/s-2002-36350
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Agents from Plants. III. Trichothecenes fromFicus fistulosaandRhaphidophora decursiva

Abstract: Bioassay-directed fractionation of an extract prepared from the dried leaves and stem barks of Ficus fistulosa Reinw. ex Blume (Moraceae) led to the isolation of verrucarin L acetate (1), together with 3alpha-hydroxyisohop-22(29)-en-24-oic acid, 3beta-gluco-sitosterol, 3,4-dihydro-6,7-dimethoxyisocarbostyril, 3,4,5-trimethoxybenzyl alcohol, alpha-methyl-3,4,5-trimethoxybenzyl alcohol, indole-3-carboxaldehyde, palmanine, and aurantiamide acetate. Roridin E (2) was identified in a subfraction from the dried leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 17 publications
2
37
0
1
Order By: Relevance
“…Rhaphidecursinols A (11) and B (12), grandisin (13), epigrandisin (14) and decursivine (15) also showed activities against P. falciparum (D6 and W2) with IC50 values of 3.4-12.9 μM and cytotoxicity of ED50 values of 23.9-37.0 μM against KB cells with an exception of compound 14, which showed no antimalarial activity against D6 strain at 23 μM. According to the further investigation of Zhang et al [24], a potent but toxic trichothecene compound, roridin E (3) was identified from the same plant extract (Figure 2). The investigators determined that the compound was able to inhibit parasite growth with IC50 values in the sub-nano molar range.…”
Section: Araceae Familymentioning
confidence: 95%
See 1 more Smart Citation
“…Rhaphidecursinols A (11) and B (12), grandisin (13), epigrandisin (14) and decursivine (15) also showed activities against P. falciparum (D6 and W2) with IC50 values of 3.4-12.9 μM and cytotoxicity of ED50 values of 23.9-37.0 μM against KB cells with an exception of compound 14, which showed no antimalarial activity against D6 strain at 23 μM. According to the further investigation of Zhang et al [24], a potent but toxic trichothecene compound, roridin E (3) was identified from the same plant extract (Figure 2). The investigators determined that the compound was able to inhibit parasite growth with IC50 values in the sub-nano molar range.…”
Section: Araceae Familymentioning
confidence: 95%
“…For example, polysyphorin (1) and rhaphidecurperoxin (2), isolated from Rhaphidophora decursiva (Araceae), showed antimalarial activities of 0.37 and 0.42 µg/mL against the W2 clones of P. falciparum, respectively ( Figure 2) [22]. Two trichothecenes, roridin E (3) from Rhaphidophora decursiva (Araceae) and verrucarin L acetate (4) from Ficus fistulosa (Moraceae), were found to potently inhibit the parasite growth with IC50 values in the sub-nano molar range [24]. De-replication to avoid duplication of previous efforts is an essential step in drug discovery protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids [2 -7], flavonoids [8 -15], coumarins [16 -18], phenylpropanoids [19], lignans [13] [20], chromones [9] [11], triterpenoids [21 -28], sesquiterpenoids [29], and monoterpenoids [30] [31] are widely distributed in plants of the genus Ficus. Some isolates exhibited biological activities, including antioxidant [27] [32], anti-inflammatory [33] [34], cytotoxicity [4] [9], antibacterial [10], antimalaria [2] [34] [35], and antidiabetic activities [36]. However, the chemical constituents and biological activities of F. nervosa have never been investigated.…”
Section: Secondary Metabolites and Antimycobacterial Activities From mentioning
confidence: 99%
“…ex Bl. (Moraceae) [5], Nauclea orientalis (L.) L. (Rubiaceae) [6], Grewia bilamellata Gagnep. (Tiliaceae) [7], and Rourea minor (Gaertn) Aubl.…”
unclassified
“…The coupling constant (J ¼ 6.16) of HÀC(7') and HÀC(8') suggested a cisconfiguration, which was supported by the NOE effect between HÀC(7') and HÀC(8'). Thus, diospyrosin (2) was determined to be (E)-3-[(6aR*,11aR*)(6a,11a-dihydro-2,10-dimethoxy-6H-benzo [4,5]furo[3,2-c]chromen-8-yl]prop-2-enal, which is a new neolignan.…”
mentioning
confidence: 99%